Historical comic’s superpowers: the creative power to communicate visually historical epics - Nedzinskaitė-Mitkė, Vaida (Creativity Studies, 2022)
Comics are an indisputable part of popular culture. But compared to any other audiovisual media products, the production of this form of entertainment is relatively cheap. Thus, on this fact alone comic book artform could be used to fill the demand for local historical genre in popular culture and, in turn, to contribute significantly to the formation of a modern national identity among the youngest generations of the country. However, that is not the only or even the best superpower of the medium when it comes to production of fictional historical epics for entertainment purposes. In this article, the author explores comic medium’s creative aspects that could be used to effectively communicate the various visual aspects of the past. Findings suggest that the most important visual medium’s communicative tool that creates a unique and immersive experience is stylisation, in tandem with spatial and temporal systems. Additionally, the author discusses the challenges and opportunities for comic media to emerge in an educational context.